On a Theorem of Arrow - Nagatani, Keizo (Review of Economic Studies, 1975)
Journal Article On a Theorem of Arrow Get access Keizo Nagatani Keizo Nagatani University of British Columbia and University of Tokyo Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 42, Issue 3, July 1975, Pages 483–485, https://doi.org/10.2307/2296862 Published: 01 July 1975